Marjolin ulcer: a case report - Beatriz Di Martino Ortiz; Rosalba Riveros; Martinez Braga Gabriela; Medina R; Mirtha Rodríguez Masi; Oilda Knopfelmacher; Lourdes Bolla de Lezcano (Our Dermatology Online, 2014)
Marjolin's ulcer is part of a group of neoplasms arising in chronic skin lesions, whether inflammatory or traumatic. Squamous cell carcinoma is the most frequently reported in the literature, it appears most frequently in burn scars, although also described in other types of lesions. We report a case of Marjolin ulcer in a male, native, 65 years old, from the Paraguayan Chaco, with antecedents of scar post trauma in youth.